2020
DOI: 10.1002/jbmr.4025
|View full text |Cite
|
Sign up to set email alerts
|

Hymenialdisine: A Marine Natural Product That Acts on Both Osteoblasts and Osteoclasts and Prevents Estrogen-Dependent Bone Loss in Mice

Abstract: Excessive osteoclast (OC) activity together with relatively weak osteoblast (OB) function are strongly connected to osteolytic diseases, including osteoporosis, tumor-induced osteolysis, and inflammatory bone erosion. Very few natural products or compounds have been shown to exert therapeutic effects on both OCs and OBs, limiting the potential development of natural compounds for clinical application. Hymenialdisine (HMD) is a marine sponge-derived natural inhibitor of protein kinases with previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Under the stimulus of upstream signaling, β-catenin accumulated in the cytoplasm and subsequently translocated to the nucleus, which brought about downstream osteogenic-related genes transcription. The inhibition of GSK-3β was proven to restore the β-catenin level to some extent, and then facilitated osteogenesis differentiation of BMSCs 58 , 59 . The OVX-rat cranial defect model further proved that the La-LDH nanohybrid scaffolds promoted the in vivo formation of the collagenous and non-collagenous organic matrix compared to the LDH scaffolds (Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the stimulus of upstream signaling, β-catenin accumulated in the cytoplasm and subsequently translocated to the nucleus, which brought about downstream osteogenic-related genes transcription. The inhibition of GSK-3β was proven to restore the β-catenin level to some extent, and then facilitated osteogenesis differentiation of BMSCs 58 , 59 . The OVX-rat cranial defect model further proved that the La-LDH nanohybrid scaffolds promoted the in vivo formation of the collagenous and non-collagenous organic matrix compared to the LDH scaffolds (Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclastogenesis assay was used routinely as reported 25 . In brief, BMMs were seeded into 96‐well plates at a density of 6 × 10 3 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoclastogenesis assay was used routinely as reported. 25 In brief, Then, cells were fixed with 2.5% glutaraldehyde, gently washed with PBS for twice and stained with TRAcP staining solution at 37°C for about 40 minutes. The cells of each group were photographed using an inverted light microscope, and osteoclast-like cells with multi-nuclei (with more than three nuclei) were scored.…”
Section: Osteoclast Differentiation and Tracp Stainingmentioning
confidence: 99%
“…Osteoporosis is a disease with a major impact, especially in the elderly population [ 45 ]. In this sense, Wang et al [ 42 ] studied the effect of hymenialdisine ( Figure 5 ; compound 41 ) in the bone health of mice. The authors observed that treated animals displayed lower levels of bone volume and trabecular thickness levels than nontreated animals.…”
Section: Marine Alkaloids With Biological Activity In Vivomentioning
confidence: 99%